PENGARUH RELATIONSHIP MARKETING TERHADAP LOYALITAS PELANGGAN PADA PT. SICEPAT DI KOTA MATARAM - Lalu Purnama Hadi; Akhmad Saufi; Baiq Handayani Rinuastuti (Master of Management, Mataram University, 2023)
This study aimed to determine the effect of relationship marketing which consists of commitment, trust, and communication on customer loyalty at PT. SiCepat in Mataram City. The subject of this research is SiCepat customers in Mataram City. The number of samples in this study were 50 respondents. Data collection techniques in this study used observation, interviews, and questionnaires which were analyzed using SmartPLS. The results of the research show that, (1) commitment to relationship marketing has a positive effect on customer loyalty, (2) trust in relationship marketing has a positive effect on customer loyalty, (3) communication on relationship marketing has a positive effect on customer loyalty.